UTILIZING GOOGLE CLASSROOM IN TEACHING READING COMPREHENSION - Muthi’ah, Muthi’ah; Rini Husroini; Zuhra (English Language Teaching for EFL Learners Journal, 2022)
Google Classroom has been a popular platform that becomes an option for online teaching media. Not only does it offer flexibility, but it also has powerful features that support the teaching and learning process. This study aims at finding out the effectiveness of Google Classroom in teaching reading comprehension. The purpose of this study is to find out whether using Google Classroom can affect the reading comprehension of the English Education Department students at a state university in South Sulawesi. The research applied quantitative method and used the purposive sampling technique. The population of this research was 101 students in the third semester. The sample was 40 students. There were 20 students in class B as the experimental class and 20 students in class A as the controlled class. In gathering the data, the researcher used reading tests in the pre-test and post-test assessment. The findings show that the students acquired pre-test scores with a mean score of 74.65, classified as fair. After receiving treatments, there was an improvement. The students achieved a mean score of 86.2. Based on the results, it can be concluded that the use of Google Classroom is considerably effective in teaching reading comprehension.